Laser Synthesis and Microfabrication of Micro/Nanostructured Materials Toward Energy Conversion and Storage - Zhao, Lili; Liu, Zhen; Chen, Duo; Liu, Fan; Yang, Zhiyuan; Li, Xiao; Yu, Haohai; Liu, Hong; Zhou, Weijia (Nano-Micro Letters, 2021)
Nanomaterials are known to exhibit a number of interesting physical and chemical properties for various applications, including energy conversion and storage, nanoscale electronics, sensors and actuators, photonics devices and even for biomedical purposes. In the past decade, laser as a synthetic technique and laser as a microfabrication technique facilitated nanomaterial preparation and nanostructure construction, including the laser processing-induced carbon and non-carbon nanomaterials, hierarchical structure construction, patterning, heteroatom doping, sputtering etching, and so on. The laser-induced nanomaterials and nanostructures have extended broad applications in electronic devices, such as light–thermal conversion, batteries, supercapacitors, sensor devices, actuators and electrocatalytic electrodes. Here, the recent developments in the laser synthesis of carbon-based and non-carbon-based nanomaterials are comprehensively summarized. An extensive overview on laser-enabled electronic devices for various applications is depicted. With the rapid progress made in the research on nanomaterial preparation through laser synthesis and laser microfabrication technologies, laser synthesis and microfabrication toward energy conversion and storage will undergo fast development. Highlights: 1 The current understanding and advances on laser synthesis of nanomaterials are summarized. 2 The laser microfabrication-enabled energy conversion and storage devices are reviewed. 3 The limitations and solutions for current laser processing of nanomaterials and other more potential development directions for laser processing are proposed.